Entomophages as a Perspective Direction of Plant Protection - Marinchenko , Tatiana (KnE Life Sciences, 2021)
Increased demand for food to feed the ever-growing population led to the development and adoption of synthetic chemicals as a quick and effective strategy of managing crop pests and diseases. Such agricultural practices have contributed to environmental pollution, which is further affecting food security, human health, and the climate. At the same time, up to 40% of crops die due to pests and plant diseases. Therefore, sustainable crop production and global food security depend on the timely implementation of the latest scientific projects in various fields of crop production including genetics, breeding, agronomy, crop physiology, crop management practices, biotechnology, and even entomology. The introduction of biological agents to protect, control and stimulate the development of agricultural crops is one of the ways of increasing the efficiency and profitability of production, reducing the environmental burden and increasing the competitiveness of producers. This is consistent with the concepts of a green economy and the sustainable development of agriculture. Since the unilateral use of chemicals does not meet today’s requirements, special attention must be paid to preventative, agrotechnical measures, as well as the use of natural factors for regulating the number of pests using parasitic and predatory insects. Domestic biotechnological developments for crop production which increase production efficiency and reduce the environmental burden are discussed. Keywords: plant growing, entomophages, protection, efficiency, ecology, ecology